2018
DOI: 10.1016/j.hpb.2018.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Decoding grade B pancreatic fistula: a clinical and economical analysis and sub-classification proposal

Abstract: LAPC, initial results suggest CDA is safe. Evaluation of the safety and efficacy of CDA in this setting is ongoing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
47
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(54 citation statements)
references
References 29 publications
5
47
1
1
Order By: Relevance
“…8 However, in the current ISGPF grading system, grade B POPF is a clinically heterogeneous condition because of its treatment-based definition. 7,9,10 A recent study from Maggino et al reported that the clinical burden of patients with grade B POPF requiring only persistent drainage over 21 days (B-drain) was distinctly lower than that of patients with grade B POPF requiring pharmacologic management or interventional procedures. 9 Moreover, van Hilst et al reported that the clinical course was comparable between patients requiring only persistent drainage over 21 days and those with biochemical leakage (BL).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…8 However, in the current ISGPF grading system, grade B POPF is a clinically heterogeneous condition because of its treatment-based definition. 7,9,10 A recent study from Maggino et al reported that the clinical burden of patients with grade B POPF requiring only persistent drainage over 21 days (B-drain) was distinctly lower than that of patients with grade B POPF requiring pharmacologic management or interventional procedures. 9 Moreover, van Hilst et al reported that the clinical course was comparable between patients requiring only persistent drainage over 21 days and those with biochemical leakage (BL).…”
mentioning
confidence: 99%
“…7,9,10 A recent study from Maggino et al reported that the clinical burden of patients with grade B POPF requiring only persistent drainage over 21 days (B-drain) was distinctly lower than that of patients with grade B POPF requiring pharmacologic management or interventional procedures. 9 Moreover, van Hilst et al reported that the clinical course was comparable between patients requiring only persistent drainage over 21 days and those with biochemical leakage (BL). 11 These findings raise concerns regarding the utility of persistent drainage over 21 days as a clinically relevant threshold in determining the clinical condition of these patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…POPF is recognized as a life-threatening complication after PD which occurs in nearly 20% patients. 32,33 The early detection of POPF improves the postoperative monitoring and the management of complications. The risk factors of POPF after PD have been much explored in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Class B and C pancreatic fistulas are defined more strictly than before. Class B pancreatic fistulas require significant clinical interventions such as continuing drainage for more than three weeks or endoscopic and percutaneous drainage [5]. Class C pancreatic fistulas refer to pancreatic fistulas requiring further surgical intervention.…”
Section: Definition Of Pancreatic Fistulamentioning
confidence: 99%